Notfallkoniotomie - chirurgisch oder doch Punktion? - Mohr, Stefan; Göring, Martin; Knapp, Jürgen (Notfall & Rettungsmedizin, 2019)
The emergency cricothyroidotomy is an invasive approach to the airway via the cricothyroid membrane to ensure oxygenation and ventilation in an emergency cannot ventilate, cannot intubate scenario. In this rare situation of failure of endotracheal intubation as well as supraglottic airways and bag valve mask ventilation cricothyroidotomy represents a life-saving technique and is indicated according to several current guidelines. In order to make a clear evidence-based recommendation in favour of a puncture technique or a surgical preparation technique in the context of emergency cricothyroidotomy, the data situation is not sufficient at the moment. A combination of both techniques and an adaptation to the given anatomical conditions may be advantageous. Sonography can be a promising and easy to learn tool for the reliable identification of the cricothyroid membrane in difficult anatomical conditions. Key for success is not primarily which of the two mentioned techniques is preferred, but rather that the users are trained and practiced in the correct indication, crew resource management and the management of complications. Complications include acute bleeding and injuries to adjacent organs as well as failure of the procedure itself.